Agreement, reliability and validity in 3 shoulder questionnaires in patients with rotator cuff disease - Ekeberg, Ole M (BioMed Central, 2008)
BACKGROUND: Self-report questionnaires play an important role as outcome measures in shoulder research. Having an estimate of the measurement error of these questionnaires is of importance when assessing follow-up results after treatment and when planning intervention studies. The aim of this study was to cross-culturally adapt the Norwegian version of the OSS and WORC questionnaire and examine and compare agreement, reliability and construct validity of the disease-specific shoulder questionnaire WORC with two commonly used shoulder questionnaires, SPADI and OSS, in patients with rotator cuff disease. METHODS: 74 patients with rotator cuff disease were recruited from the outpatient clinic of the Physical Medicine and Rehabilitation Department at Ullevaal University Hospital in Oslo, Norway. A test-retest design was used, and the questionnaires were filled out by the patients at the clinic, with a one week interval between test administrations. Agreement (repeatability coefficient), reliability (ICC) and construct validity were examined and compared for WORC, SPADI and OSS. RESULTS: Reliability analysis was restricted to the 55 patients (51 ± 10 yrs) who reported no change between test administrations according to scoring on a global scale. The agreement, reliability and construct validity was moderate for all three questionnaires with ICC ranging from 0.83 to 0.85, repeatability coefficient from 16.1 to 19.7 and Spearman rank correlations between total scores from r = 0.57 to 0.69. There was a lower degree of floor and ceiling effects in SPADI compared to WORC and OSS. CONCLUSION: We conclude that the agreement and reliability of the three shoulder questionnaires examined, WORC index, SPADI and OSS are acceptable and that differences between scores were small. The Norwegian version of the questionnaires is acceptable for assessing Norwegian-speaking patients with rotator cuff disease. The moderate agreement and construct validity should be taken into consideration when assessing follow-up results after treatment and in the planning of prospective studies.